2012
DOI: 10.1111/j.1365-2702.2012.04139.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the benefits and challenges of the role of advanced practice nurses in nurse‐led out‐of‐hours care in Hong Kong: a questionnaire study

Abstract: Findings from this study enhance understanding of the factors that hinder or facilitate advanced practice roles in out-of-hours care in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…The results in this study showed that the patients were satisfied with the APN's professional holistic approach and the health care provided, which is similar to results in other studies (Agosta, 2009;Bergman et al, 2013;Brown, 2007;Green & Davis, 2005;Schadewaldt, McInnes, Hiller, & Gardner, 2013). Christiansen, Vernon, and Jinks (2013) found that the APNs contribute to improvement of aspects as safety and quality in care, which aligns with the findings in this study. The participants described earlier experiences of poor accessibility to primary health care and long waiting times.…”
Section: Discussionsupporting
confidence: 91%
“…The results in this study showed that the patients were satisfied with the APN's professional holistic approach and the health care provided, which is similar to results in other studies (Agosta, 2009;Bergman et al, 2013;Brown, 2007;Green & Davis, 2005;Schadewaldt, McInnes, Hiller, & Gardner, 2013). Christiansen, Vernon, and Jinks (2013) found that the APNs contribute to improvement of aspects as safety and quality in care, which aligns with the findings in this study. The participants described earlier experiences of poor accessibility to primary health care and long waiting times.…”
Section: Discussionsupporting
confidence: 91%
“…(24) Research suggests that because there is a lack of a solid and informed understanding of the autonomous, independent actions of APNs when there is an absence of physician care, patients and families may experience feelings of insecurity with this care. (23) To address this potential obstacle, the results of a study evaluating the role of advanced practice nurses in Finland suggests the importance of clearly defining the role of APNs for the development of their sustainable and trusted practice. (32) Regarding the perception of doctors and nurses about the introduction of the APN role, benefits for patient care and safety, such as the optimization of actions and evidence-based practice, and an increase in professional status were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Those factors help to improve the perception of other professionals and patients about the image of the APN. (23,33) In view of the incorporation of strategic planning for coverage and universal access to health in the health systems of the countries supported by the Pan American Health Organization and the Human Resources for Health resolution that underscores the increase in the number of advanced practice nurses to provide support to health systems, this practice is recognized as of fundamental importance for reducing morbidity and mortality in primary health care. (29) Therefore, for the implementation of this practice it is necessary that a modification occurs in order to promote a broader role of nursing, which requires political support, the direction of health services, health teams, nursing teachers and professionals themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries throughout the world have also embraced the role of the APN as a cost-effective way to provide quality care that is evidence based (Aleshire & Wheeler, 2012;Christiansen, et al, 2012;Flagerstrom & Glasberg, 2011;Matthews, 2012;Nardi & Diallo, 2014). It is interesting to note that APNs in other countries are experiencing many of the same issues that US APNs are experiencing; issues of education requirements, role of the APN, licensing, scope of practice, and acceptance by the medical community as well as by the public.…”
Section: Apn Issuesmentioning
confidence: 99%
“…Tudi v drugih državah po svetu so sprejeli vlogo APN, ki predstavljajo cenovno sprejemljivo in učinkovito zdravstveno osebje, ki zagotavlja z dokazi podprto kakovostno zdravstveno oskrbo (Aleshire & Wheeler, 2012;Christiansen, et al, 2012;Flagerstrom & Glasberg, 2011;Matthews, 2012;Nardi & Diallo, 2014). Zanimivo je dejstvo, da se APN tudi v drugih državah srečujejo s podobnimi problemi kot v ZDA.…”
Section: Diplomirane Medicinske Sestre/ Diplomirani Zdravstveniki Z Nunclassified